Nurses’ Work Motivation and their Demographics: Basis for Human Resource Management - Dayrit, Richard Dennis Juinio (Advances in Social Sciences Research Journal, 2021)
This study assessed the level of work motivation of 245 nurses generated through snowball sampling in a tertiary government hospital in Hail City, Kingdom of Saudi Arabia using the Multidimensional Work Motivation Scale. The results indicated that the nurses had a low level of amotivation, moderate levels of all subtypes of extrinsic regulation, and moderate levels of intrinsic regulation leading to an overall moderate level of work motivation. Significant differences in levels of work motivation were observed in the domain of amotivation when nurses were grouped according to work position; in the domain of extrinsic motivation-social when nurses were grouped according to civil status, monthly salary and years of experience in the institution; in the domain of extrinsic motivation-material when nurses were grouped according to years of experience in the institution; in the domain of introjected regulation when the nurses were grouped according to age and civil status; and in the domains of identified regulation and intrinsic motivation when they were grouped according to civil status (p≤0.05). Hospital administrators need to implement specific human resource management strategies such as: (1) the implementation of a fair system of staff performance appraisal through management by objectives; (2) the provision of training needs of staff for learning and career development; (3) mechanisms that foster social support among healthcare teams; (4) mechanisms that promote nurse engagement, autonomy and empowerment; and (5) a consistent and equitable system of rewards and promotions in order to enhance the level of work motivation of nurses.